The role of confidence in tax return preparation - Hageman, Amy M. (Emerald Group Publishing, 2011)
This paper investigates the nature of tax preparers’ confidence, as well as how the introduction of a tax decision support system (TDSS) affects tax preparers’ confidence levels. Psychological theories of confidence (e.g., Einhorn & Hogarth, 1978) are drawn upon to develop predictions regarding the role of process (ex-ante) and outcome (ex-post) confidence in tax return preparation. An experimental methodology is used with 114 inexperienced and experienced participants that prepare an individual income tax return manually or with tax preparation software (a TDSS). Less experienced tax preparers have lower levels of ex-ante confidence, and are more likely to be overconfident in the accuracy of their performance. Furthermore, when examining only the participants that made errors in their tax return preparation task, those that prepare the return with the TDSS are significantly more likely to be overconfident in their performance. These results support the predictions of Noga & Arnold (2002) and suggest that inexperienced users’ over-reliance on a TDSS (Masselli et al., 2002) may be due to individuals’ overconfidence in the accuracy of their performance with the software.
Keywords: Tax return preparation; Confidence; Tax preparation software; Tax decision support system (TDSS)